Assessment of an Algorithm for Prescription of Oral Anticoagulation for Patients With Atrial Fibrillation in Emergency Departments - Atzema, Clare L. (JAMA Netw Open, 2020)
This retrospective study uses a Canadian reporting system to validate an algorithm that identifies oral anticoagulation prescriptions given to patients with atrial fibrillation treated in emergency departments.